2019
DOI: 10.3390/ijms21010041
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Effects of Microalgae

Abstract: In recent years, microalgae have attracted great interest for their potential applications in nutraceutical and pharmaceutical industry as an interesting source of bioactive medicinal products and food ingredients with anti-oxidant, anti-inflammatory, anti-cancer, and anti-microbial properties. One potential application for bioactive microalgae compounds is obesity treatment. This review gathers together in vitro and in vivo studies which address the anti-obesity effects of microalgae extracts. The scientific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…Microalgae produce various compounds that can be consumed as food products. These compounds are not only used to supplement the diet but are also used in the prevention or treatment of diseases and/or disorders 1 , 2 . Euglena gracilis ( E. gracilis ) is a candidate fast-proliferating microalga, besides Chlorella and Spirulina , and research into its commercial cultivation is ongoing 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Microalgae produce various compounds that can be consumed as food products. These compounds are not only used to supplement the diet but are also used in the prevention or treatment of diseases and/or disorders 1 , 2 . Euglena gracilis ( E. gracilis ) is a candidate fast-proliferating microalga, besides Chlorella and Spirulina , and research into its commercial cultivation is ongoing 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies indicate that Arthrospira maxima and platensis , as well as other microalgae, exert their anti-obesity effects via the reduction of both adipogenesis in white adipose tissue (WAT) and lipogenesis in WAT and brown adipose tissue (BAT). They increase lipolysis in WAT, lipid oxidation in WAT and skeletal muscle, and also thermogenesis and mitochondriogenesis in WAT, BAT, and skeletal muscle [ 19 ]. An ethanolic extract of A. maxima (150 or 450 mg/kg/day) reduced body weight, both subcutaneous and visceral adipose tissue, blood fasting glucose and lipid concentrations in mice fed a high-fat (HF) diet [ 20 ].…”
Section: Spirulina ( Arthrospira ) and Metabolimentioning
confidence: 99%
“…Marine products have great attention due to their potential applications in functional foods and food additives because of their health-promoting properties, including antiobesity, antioxidant, anti-inflammatory, and anticancer effects [ 61 ]. Recent studies have revealed new roles of marine products in adipocyte browning and energy balance ( Table 3 ).…”
Section: Marine Products That Induce Adipose Browningmentioning
confidence: 99%
“…Spirulina maxima is a microalga that is abundant in essential nutrients and includes pigment proteins including chlorophyll a and C-phycocyanin [ 67 , 68 ]. Studies have reported that S. maxima exhibit antioxidant, anticancer, and neuroprotective effects [ 61 ] but its potential in obesity and adipose tissues is unclear. A recent study examined the ethanol extract of S. maxima on adipogenesis, lipogenesis, and browning using in vitro and in vivo mouse models [ 63 ].…”
Section: Marine Products That Induce Adipose Browningmentioning
confidence: 99%